Correlation Between Settlement Environmental Quality and Acute Respiratory Infection (ARI) Disease of Gayamsari Sub-District, Semarang - Ary Mandhara Putra; Bitta Pigawati (Geoplanning: Journal of Geomatics and Planning, 2021)
Settlement area with high population density and situated in unfeasible location cause the quality of settlement environment to be low. The low quality of settlement environment has the potential to cause Acute Respiratory Infection (ARI). This study aimed to explain the correlation of settlement environmental quality and incidence of ARI disease in Gayamsari Sub-District, Semarang. This research used a quantitative descriptive spatial approach by using remote sensing technique and Geographic Information System (GIS).  The result showed that there is a high and significant correlation between settlement environmental quality and acute respiratory infection (ARI) Incidence, especially happened in Kaligawe and Tambakrejo village.